Miwiti Creative Space Semarang: Modern Business With Fundraising Capital (Crowdfunding) - Irawan, Joseph Aldo; Pamungkas, Imang Dapit; Khotimah, Novi; Samsiah; Agustian, Adinda; Danurdara, Ananta Budhi; Sukmadi; Darmawan, Haryadi; Hapsari, Dian Indriana (Journal of Consumer Studies and Applied Marketing, 2024)
The tourism business plays a significant role in economic income, with creative spaces emerging as a notable trend in the industry. The Ministry of Tourism and Creative Economy promotes these spaces to support creative economy entrepreneurs. One critical issue aspiring entrepreneurs face is securing capital, leading to the adoption of crowdfunding methods. Miwiti Creative Spaces, a pioneer in Semarang, has explored this fundraising method. This study investigates the application of crowdfunding methods in the contemporary tourism business. Employing a qualitative descriptive method supported by documentation, the research identifies various stages implemented by Miwiti Creative Spaces in applying crowdfunding to meet their needs. The findings indicate that crowdfunding can effectively address funding challenges for new entrepreneurs. Specifically, the study reveals that Miwiti Creative Spaces follows a structured approach, beginning with identifying potential projects suitable for crowdfunding. They then plan strategically to reach potential backers, leveraging social media and other digital platforms for outreach. The process involves continuous communication with supporters to build trust and maintain interest, ensuring transparency and accountability throughout the funding period. The study underscores that crowdfunding provides a financial solution and fosters community and engagement among supporters. This can enhance the visibility and reputation of new ventures. Consequently, the research concludes that crowdfunding is a viable and beneficial method for overcoming funding barriers in the creative economy sector. This insight is valuable for policymakers and entrepreneurs leveraging crowdfunding for business development.